MENGUAK DAMPAK TIKTOK TERHADAP MINAT BELAJAR SISWA MADRASAH IBTIDAIYYAH DAN UPAYA MENARIK GENERASI DIGITAL TERHADAP MINAT BELAJAR - Nasir, Muhammad Fikri Abdun (Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2025)
Using TikTok can influence changes in children's behavior, both moral and social behavior around them. Therefore, it is very important for teachers and parents to carry out careful, ongoing supervision and limit children's use of TikTok. Based on research results from several researchers, it is known that TikTok has a significant influence on students' interest in learning, giving rise to concerns among teachers regarding its impact on learning outcomes. The findings of this research indicate the need to change the learning system or process to make it more innovative, with the aim of increasing students' interest in learning.